Penghiburan Sejati Orang Percaya Menurut Katekismus Heidelberg [True Comfort for Believers According to the Heidelberg Catechism] - Musa Sinar Tarigan (Universitas Pelita Harapan, 2021)
Comfort is necessity for every believer in this changing world. Believers are constantly faced with various challenges and struggles in life that are not easy. Since the world keeps changing that require the readiness of believers to react this changing. In addition, believers continue to struggle against sinful desires and lead holy and blameless life to get to know Christ more. The Bible teaches that God is with believers throughout the ages. This paper will show that God who has redeemed believers through Christ's sacrifice on the cross has the power to maintain the life of the believer in all circumstances so that God becomes the source of hope for the believer throughout his life, and God also enables the believer, strength, joy in all situations with an abundance of thanksgiving. The Heidelberg Catechism states that the believer's true comfort is only in Christ.